Media Sosial Sebagai Sarana Penunjang Pemasaran Serta Promosi pada UMKM Toko Busana - Rambe, Riswan; As-Singkily, Herdi; Auliadi, Rusdi (As-Syirkah: Islamic Economic & Financial Journal, 2024)
Technology tools in this day and age has a lot of positive effects or impacts to opportunities in making it easier for humans to find and provide various sources of information, one of which is included in this case is social media such as Facebook, Instagram. In this social media can do marketing products through various up-to-date online websites, in social media is a supporting tool for promoting goods and products in umkm to date. nowadays. The research conducted intends to find out that this social media is one of the supporting tools for marketing fashion store products. In managing and promoting fashion store products owned by Mrs. Jannah using social media applications, one of which is often used is faceboook and Instagram, besides that Mrs. Jannah often uses the Facebook application as the main means of promoting goods and products, because mothers or the surrounding environment use the application more often than other applications. use the application than other applications. This research using a qualitative research method with a descriptive approach, with this means that researchers have conducted interviews to conduct and analyze data that can be used by researchers to support research. analyze data that can be used by researchers in supporting effective, accurate and effective research , hat is effective, accurate and effective.